Histopathologic Features are more Important Prognostic Factors than Primary Tumour Location in Gastro-oesophageal Adenocarcinoma Treated with Preoperative Chemoradiation and Surgery - Vošmik, Milan; Laco, Jan; Sirák, Igor; Dvořák, Josef; Lochman, Petr; Hodek, Miroslav; Malá, Petra; Rejchrt, Stanislav; Repák, Rudolf; Leško, Michal; Ferko, Alexander; Ryška, Aleš; et al. (Pathology oncology research, 2018)
The aim of present study was to evaluate the impact of primary tumour location and other factors on the outcome of preoperative chemoradiation followed by surgery in adenocarcinomas of distal oesophagus, gastro-oesophageal junction and stomach. We retrospectively reviewed the institutional patient database. The therapeutic response was re-evaluated as a percentage of residual tumor cells in surgical resection specimens. Overall survival (OS) and disease-free survival (DFS) were assessed. The effect primary tumour location, clinical and pathological TNM stage, and histopathological factors (histological type, grade, angioinvasion, perineural invasion, tumour response) on treatment outcome were evaluated. A total of 108 patients underwent preoperative chemoradiation for adenocarcinoma of distal oesophagus, gastro-oesophageal junction or stomach. The median prescribed dose of radiation was 45 Gy. The concurrent chemotherapy consisted of 5-fluorouracil +/- cisplatin +/- taxanes. R0 resection was achieved in 80 patients (74%). The complete response was observed in 19%. The median follow-up was 50.8 months. Three-year and 5-year OS and DFS were 36.2% and 25.3%; and 28.1% and 23.7%, respectively. Pretreatment T-stage, pathological N-stage, radicality of resection, histological subtype, grade, angioinvasion and perineural invasion, were identified as statistical significant OS predictors in univariate analysis; pathological N-stage, radicality of resection and angioinvasion, in multivariate analysis. The primary tumor location did not influence the prognosis. The pathologic response to chemoradiation had borderline significance. In conclusion, no prognostic impact of primary tumour location, in contrast to other investigated factors, was evident in the present study. The most important predictors of prognosis were angioinvasion status and pN-stage.
Keywords: chirurgie trávicího traktu; nádory žaludku; Adenocarcinoma; neoadjuvantní terapie; Humans; Esophagogastric Junction; lidé středního věku; Gastro-oesophageal junction cancer; Female; Aged; dospělí; nádory jícnu; gastroezofageální junkce; výsledek terapie; senioři; lidé; adjuvantní chemoradioterapie; přežití bez známek nemoci; Esophageal Neoplasms; Gastric cancer; Adult; ženské pohlaví; Male; Middle Aged; Retrospective Studies; prognóza; Treatment Outcome; Aged, 80 and over; Neoadjuvant Therapy; Disease-Free Survival; senioři nad 80 let; Preoperative chemoradiation; adenokarcinom; retrospektivní studie; Distal oesophageal cancer; Prognostic factor; mužské pohlaví; Chemoradiotherapy, Adjuvant; Digestive System Surgical Procedures; Stomach Neoplasms; Prognosis